Level of knowledge on preeclampsia following health education through a WhatsApp group - Anggi Wilis Prihazty; Atika; Ivon Diah Wittiarika; Ernawati (Universitas Airlangga, 2024)
HIGHLIGHTS • WhatsApp groups can effectively overcome the constraints of antenatal care in delivering health education to pregnant women. • The scope of health information about pregnancy should be expanded as this study has shown that it enhances their level of knowledge.   ABSTRACT Objective: Hypertension in pregnancy, including preeclampsia, is the third most common cause of maternal mortality in Indonesia; one of the problems is low preeclampsia knowledge in the community. WhatsApp, as a social media platform, could facilitate spearheading promotive and preventive efforts, especially for high-risk mothers in the community. This study aimed to analyze the difference in levels of knowledge after receiving education through WhatsApp groups. Materials and Methods: This was a pre-experimental study using one group pre-test and one post-test design. The sample size was 58 high-risk pregnant women in one of the Public Health Centers in Surabaya. Respondents completed a preeclampsia knowledge questionnaire before and after receiving health education via WhatsApp group for 12 days. The results were analyzed using the Wilcoxon signed rank test, Mann-Whitney U-Test, and Kruskal Wallis test. Results: Most respondents had good knowledge about preeclampsia before and improved after intervention. All respondents had a difference in knowledge before and after the intervention (p <0.001). The only factor that showed a difference in the initial knowledge level about preeclampsia was previous exposure to preeclampsia information (p=0.014). Conclusion: Health education through WhatsApp groups can be considered to be provided as it has been proven effective in increasing the knowledge among high-risk pregnant women about preeclampsia. as it has been proven effective in increasing the knowledge among high-risk pregnant women about preeclampsia.